2014
DOI: 10.1186/2045-7022-4-3
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 producing T cells correlate with polysensitization but not with bronchial hyperresponsiveness in patients with allergic rhinitis

Abstract: BackgroundTh2-type T cell response has a considerable role in atopic diseases. The involvement of Th17 and IL-17 in atopy process provided new understanding of allergic diseases. Bronchial hyperresponsiveness is quite common in allergic rhinitis. We aimed to explore the expression of IL-17 producing CD3+ CD4+ T cells in peripheral blood of rhinitic patients, with/without bronchial hyperresponsiveness and sensitized to common allergens, as this relationship has not been examined.MethodsSixty one patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…A human population of Th17 cells that express CD39 also are resistant to the effects of adenosine as a consequence of low expression of A 2A Rs (30). Moreover, IL-17 may be particularly important for controlling airway hyperresponsiveness (43). The findings also demonstrate that CGS administered at a dose of 100 ng·kg Ϫ1 ·min Ϫ1 does not have significant direct bronchodilator effects.…”
Section: Myeloid Cells As Targets Ofmentioning
confidence: 90%
“…A human population of Th17 cells that express CD39 also are resistant to the effects of adenosine as a consequence of low expression of A 2A Rs (30). Moreover, IL-17 may be particularly important for controlling airway hyperresponsiveness (43). The findings also demonstrate that CGS administered at a dose of 100 ng·kg Ϫ1 ·min Ϫ1 does not have significant direct bronchodilator effects.…”
Section: Myeloid Cells As Targets Ofmentioning
confidence: 90%
“…It has been proved that goblet cell hyperplasia, mast cell infiltration, Th-2, Th-9 and Th-17 polarization are recognized as important features of AR 3 5 22 23 . In the present study, significantly increased goblet cell hyperplasia, mast cell infiltration, IL-4, IL-9 and IL-17 levels were found in AR mice compared with normal control mice, which is consistent with previous reports 3 5 22 23 . In addition, MUC5AC and tryptase mRNA levels were significantly upregulated in AR mice compared with normal control mice, further confirming that goblet cell hyperplasia and mast cell infiltration are involved in the pathogenesis of AR.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most of these studies, patients allergic to perennial allergens [27, 28] or sensitive to seasonal and perennial allergens were involved [29]. Another study describes the influence of perennial allergen challenge by nebulization on Th 17 cells [30], however, less is known about changes over time caused by natural seasonal allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Another study describes the influence of perennial allergen challenge by nebulization on Th 17 cells [30], however, less is known about changes over time caused by natural seasonal allergen exposure. It was shown that the percentage of IL-17A-producing CD4+ T cells may also depend on polysensitization of the patients and on patient’s sex [29]. Although an increased serum IL-17 level was observed in patients sensitive to perennial allergens, pollen allergens did not cause significant changes [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation